2023
DOI: 10.3390/jcm12237287
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Iron Replacement Therapy on HbA1c Levels in Diabetic and Nondiabetic Patients: A Systematic Review and Meta-Analysis

Amani M. AlQarni,
Amal A. Alghamdi,
Hussain J. Aljubran
et al.

Abstract: Background: Several studies have reported that iron-deficiency anemia (IDA) and its treatment might lead to a distorted reading of glycated hemoglobin (HbA1c) value. Hence, this review aims to systematically investigate the effect of iron replacement therapy (IRT) on HbA1c levels, as the literature is deficient in assessing this clinical phenomenon. Methods: An electronic search of the Cochrane, MEDLINE, and Embase databases was conducted by four independent authors. Results: Among the 8332 articles identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(134 reference statements)
1
1
0
Order By: Relevance
“…Studies have reported a decrease in HbA1c after undergoing IRT, suggesting that it can effectively reduce HbA1c levels. 46 Similarly, this study found that there was a significant decrease in HbA1c after receiving IRT in pregnant women with IDA. These findings could be attributed to the fact that iron plays a critical role in creating haemoglobin.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Studies have reported a decrease in HbA1c after undergoing IRT, suggesting that it can effectively reduce HbA1c levels. 46 Similarly, this study found that there was a significant decrease in HbA1c after receiving IRT in pregnant women with IDA. These findings could be attributed to the fact that iron plays a critical role in creating haemoglobin.…”
supporting
confidence: 57%
“…[41][42][43][44][45] The literature contains different systematic reviews and meta-analyses that discuss the correlation between IDA and HbA1c levels in this group. [46][47][48][49][50] However, a few studies have discussed their correlation in pregnant women with IDA. 17,[21][22][23][24][25][26] This study conducted a comprehensive review of published data on the effect of IDA on HbA1c among pregnant versus non-pregnant women.…”
Section: Discussionmentioning
confidence: 99%